Oil well testing handbook - Chaudhry, Amanat U. (Gulf Professional Pub., 2004)
This is a valuable addition to any reservoir engineer's library, containing the basics of well testing methods as well as all of the latest developments in the field. Not only are ""evergreen"" subjects, such as layered reservoirs, naturally fractured reservoirs, and wellbore effects, covered in depth, but newer developments, such as well testing for horizontal wells, are covered in full chapters.*Covers real-life examples and cases *The most up-to-date information on oil well testing available*The perfect reference for the engineer or textbook for the petroleum engine.